Women's utilisation of prevention of mother-to-child transmission of human immunodeficiency virus services in Addis Ababa, Ethiopia - Tefera G. Negash; Valerie J. Ehlers (AOSIS, 2018)
Background: Human immunodeficiency virus (HIV) mother-to-child transmission (MTCT) can be prevented when HIV-positive pregnant women use effective prevention of mother-to-child transmission (PMTCT) of HIV services. Approximately 50% of HIV-positive pregnant women used free PMTCT services in Ethiopia.   Aim: This study attempted to identify factors influencing women's utilisation of PMTCT services. Addressing such factors could enable more Ethiopian women to use PMTCT services. The study investigated whether women's utilisation of services was affected by socio-demographic issues, their partners' known HIV status, disclosure of their HIV-positive status, stigma and discrimination, and satisfaction with services.   Setting: Prenatal clinics in Addis Ababa, Ethiopia.   Methods: A quantitative, cross-sectional study design was used and 384 questionnaires were completed by women who used PMTCT services in Addis Ababa.   Results: No socio-demographic characteristic prevented women's utilisation of PMTCT services, nor did stigma, discrimination or disclosure of their HIV-positive status. Most respondents' partners with unknown HIV status did not know that the respondents used PMTCT services. Most women were satisfied with the PMTCT services.   Conclusions: Prevention of mother-to-child transmission services should remain accessible to all HIV-positive women in Ethiopia. Concurrent HIV partner testing should be encouraged with appropriate counselling. HIV-positive pregnant women should be encouraged to disclose their status to their partners so that they need not use PMTCT services secretly. Patients' high levels of satisfaction with PMTCT services are a good indicator for rolling out PMTCT initiatives at other facilities. Future research should focus on HIV-positive pregnant women who do not use PMTCT services.